IMPLEMENTASI PELAPORAN HASIL ASESMEN BERBASIS E-RAPOR DI SMAN 9 BALIKPAPAN UTARA - Diah Rusmala Dewi; Sukiman Sukiman (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2021)
This article aims to discuss the implementation of e-rapor based assessment result reporting at SMAN 9 Balikpapan Utara. This research is a field research with qualitative research methods that are descriptive-analytic. This research shows that the implementation of e-rapor based assessment result reporting at SMAN 9 Balikpapan Utara is supported by adequate facilities and infrastructure, the ability of human resources that is good enough in operating these devices and there are school administrators who have adequate understanding of the operation of technology. Overall, the implementation of the e-Rapor at SMAN 9 Balikpapan Utara is quite good and effective where the e-Report is sufficient to help the teacher's task in the process of managing and reporting the assessment results. However, there are still a few obstacles in the application process such as technical constraints at the beginning of implementation, especially from elderly teachers. The solution to overcome these obstacles is to socialize and provide assistance by those who are more experts.